Функційна диференціація інструментальних семантико-синтаксичних відношень - Масицька, Тетяна; Masytska, Tatiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано функційну диференціацію інструментальних семантико-синтаксичних відношень. Визначено основні семантичні групи предикатів, що формують інструментальну семантичну залежність у функціях знаряддя дії, засобу переміщення, допоміжного матеріалу та посередництва. In this article we had analyzed the functional differentiation of instrumental semantic-syntactic relations. The basic semantic predicate groups, which form an instrumental semantic dependency in a variety of functional manifestations, were defined: an instrument of action, means of hauling, auxiliary materials and mediation. We had found out that the selection of elementary and non-elementary varieties of simple sentence depends on syntactic and semantic dependence which forms the predicate that is why the elementary simple sentences of semantic-syntactic structure differ from the basic simple sentences of formal syntactic structure. According to the study we had concluded that for the instrumental semantic dependence the function of semantic tools and means of hauling is most clearly formally expressed. All peculiarities of instrumental semantic and syntactic relations in a variety of functional displays of primarily depend on the semantics of the predicate.
The functional differentiation of instrumental semanticsyntactic relations
Keywords: семантико-синтаксична структура речення; семантико-синтаксичні відношення; просте елементарне речення; предикат; інструментальна семантична залежність; semantic-syntactic structure of sentence; design proposals; elementary of simple sentence; predicate; instrumental in the function of the tool